(untitled) (Research, Society and Development, 2022)
This text discusses the results of a didactic-pedagogical dialogue, based on the game “Atomic Bingo”. The aim of this study was to familiarize and introduce studies on the physicochemical properties of the elements arranged in the periodic table. Thus, we prepared a series of cards, with information on these elements, to be used in the game. We developed activities in 9th grade classes of Elementary School, in a Basic Education school in the city of Uberlândia, Minas Gerais. For purposes of comparison and feasibility of the game, we also developed the proposal in 3rd grade high school classes. In total, there were six applications in the basic education school, with different scenarios. We consider that the activities carried out were important mechanisms to enable the insertion of students as protagonists in the teaching-learning process, overcoming the conventional, pragmatic and, many times, memoristic view that still prevails in Brazilian schools.